The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2002
DOI: 10.1097/00005373-200203000-00019
|View full text |Cite
|
Sign up to set email alerts
|

Complications of Plate Fixation in Metacarpal Fractures

Abstract: Despite technical advances in implant material, design, and instrumentation, plate fixation of metacarpal fractures remains fraught with complications and unsatisfactory results.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
114
1
7

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 127 publications
(129 citation statements)
references
References 11 publications
7
114
1
7
Order By: Relevance
“…However, plate fixation seems prone to high rates of stiffness, adhesions, and a higher rate of surgical re-interventions (up to 14%). These soft-tissue complications after plate fixation are observed in other studies as well [5,6]. Our findings suggest that antegrade intramedullary K-wire fixation with subcutaneous burying of K-wire ends does not bear the negative characteristics of transverse pinning nor open reduction and plate fixation.…”
Section: Discussionsupporting
confidence: 74%
See 2 more Smart Citations
“…However, plate fixation seems prone to high rates of stiffness, adhesions, and a higher rate of surgical re-interventions (up to 14%). These soft-tissue complications after plate fixation are observed in other studies as well [5,6]. Our findings suggest that antegrade intramedullary K-wire fixation with subcutaneous burying of K-wire ends does not bear the negative characteristics of transverse pinning nor open reduction and plate fixation.…”
Section: Discussionsupporting
confidence: 74%
“…The incidence of our complications appears to be lower compared to other frequently used techniques such as plate fixation and transverse pinning [3,5,8]. Bone-healing disorders after surgical treatment of metacarpal shaft fractures in general are rare.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…More serious complications are rare, with nonunion, infection and tendon rupture each comprising 1.6 % of complications reported. Fusetti et al reviewed 105 non-thumb metacarpal fractures in 2002, and found a 32 % complication rate [16]. The most common complication was poor healing, with 15 % of patients split evenly between malunion and nonunion [16].…”
Section: Complicationsmentioning
confidence: 99%
“…There may be pseudo clawing, cramping, loss of endurance and weakness of the hand. [22,24] A non compliant patient is another indication for surgery. [29] We have conducted the retrospective review of 143 isolated extra-articular displaced fifth metacarpal neck fractures with or without soft tissue injury.…”
Section: Introductionmentioning
confidence: 99%